Rapa'i Daboih: Its Background History and Development in North Aceh - Azhari, Teuku (FISIP Universitas Malikussaleh, 2021)
The Indonesian is a nation that is very rich in culture. Rapa’i Daboih is one of the customs and cultures that developed in Acehnese society which demonstrates the magic of the immune dance and is played by 6-8 people in groups. This research is conducted to preserve the Rapa’i Daboih culture and pass it on to the younger generation since it is starting to lose its grip upon the eyes of the Acehnese people. This study aims to explore the background history and development of Rapa’i Daboih in Aceh, how it existed and has grown, up to the current era. The study brings about two main objectives; a) to understand the implementation and procedures of Rapa’i Daboih; b) to study the background history of Rapa’i Daboih and its early development in Aceh, especially in North Aceh. This study was conducted in Ulee Pulo dan Paloh Lada village, two villages in the North Aceh district. The study undertook a conventional qualitative approach method starting with an interview with actors in the subject and followed by observation and documentation of their activities in the field.ABSTRAKIndonesia merupakan bangsa yang sangat kaya akan budaya. Rapa’i Daboih merupakan salah satu adat dan budaya yang berkembang di masyarakat Aceh yang mempertunjukkan kesaktian tarian kebal, dan dimainkan oleh 6-8 orang secara berkelompok. Penelitian ini dilakukan untuk melestarikan budaya Rapa’i Daboih dan mewariskannya kepada generasi muda, karena sudah mulai kehilangan cengkeramannya pada masyarakat Aceh. Penelitian ini bertujuan untuk menggali latar belakang sejarah dan perkembangan Rapa’i Daboih di Aceh, asal muasal munculnya, dan perkembangannya hingga saat ini. Studi ini memiliki dua tujuan utama; a) memahami pelaksanaan dan prosedur Rapa’i Daboih; b) mempelajari latar belakang sejarah Rapa’i Daboih dan awal perkembanganya di Aceh, khususnya di Aceh Utara. Penelitian ini dilakukan di Desa Ulee Pulo dan Paloh Lada, dua desa di Kabupaten Aceh Utara. Penelitian ini menggunakan metode pendekatan kualitatif konvensional yang diawali dengan wawancara dengan aktor-aktor yang menjadi subjek penelitian dan dilanjutkan dengan observasi dan dokumentasi kegiatan mereka di lapangan.